Factors Influencing Online Buying Behavior: A Study on Bangladeshi Consumers (American Journal of Economics and Business Innovation, 2025)
The study focuses on understanding the major factors which influence the consumer-purchasing behavior in online-shopping with respect to e-commerce as it growing trend in Bangladesh environment. The primary purpose of this study is deciphering how perceived value, perceived risk, and the individual’s personal characteristics influence consumer online purchase decisions. A quantitative methodology was conducted and data were gathered through a structured questionnaire from 150 internet consumers. SPSS was used for the data analysis; correlations and multiple regressions were used to assess the interrelationships among variables. The results indicate that Perceived value meaningfully and definitely affects purchase aim and that estimated risk significantly and negatively influences purchase intention. Individuals’ income and familiarity with the internet matter too. The results offer some useful implications for e-retailers to increase satisfaction and decrease risk perceptions. Practical implications are provided for targeted marketing strategies. The model could be advanced with integrating cultural or technological factors for more accurate prediction of online consumer behavior in Bangladesh.